Production of medical Sc radioisotopes with an alpha particle beam. (December 2016) - Szkliniarz, Katarzyna; Sitarz, Mateusz; Walczak, Rafał; Jastrzębski, Jerzy; Bilewicz, Aleksander; Choiński, Jarosław; Jakubowski, Andrzej; Majkowska, Agnieszka; Stolarz, Anna; Trzcińska, Agnieszka; Zipper, Wiktor
Abstract: The internal α-particle beam of the Warsaw Heavy Ion Cyclotron was used to produce research quantities of the medically interesting Sc radioisotopes from natural Ca and K and isotopically enriched 42 Ca targets. The targets were made of metallic calcium, calcium carbonate and potassium chloride. New data on the production yields and impurities generated during the target irradiations are presented for the positron emitters 43 Sc, 44 g Sc and 44 m Sc. The different paths for the production of the long lived 44 m Sc/ 44 g Sc in vivo generator, proposed by the ARRONAX team, using proton and deuteron beams as well as alpha-particle beams are discussed. Due to the larger angular momentum transfer in the formation of the compound nucleus in the case of the alpha particle induced reactions, the isomeric ratio of 44 m Sc/ 44 g Sc at a bombarding energy of 29 MeV is five times larger than previously determined for a deuteron beam and twenty times larger than for proton induced reactions on enriched CaCO3 targets. Therefore, formation of this generator via the alpha-particle route seems a very attractive way to form these isotopes. The experimental data presented here are compared with theoretical predictions made using the EMPIRE evaporation code. Reasonable agreement is generally observed. Highlights: The α-particle beam of 20 MeV can produce 100 MBq/µAh of 43 Sc PET radioisotope on nat CaCO3 target. 43 Sc from nat CaCO3 and 4 h α-beam irradiation has the radionuclidic purity exceeding 99.95% at EOB. For a 29 MeV α-particle beam on a 42 CaCO3 target the Thick Target Yield ratio for 44m Sc/ 44g Sc is above 1/10.